Identification of the genomic region under epigenetic regulation during non‐alcoholic fatty liver disease progression. Issue 3 (17th November 2017) - Hotta, Kikuko; Kitamoto, Takuya; Kitamoto, Aya; Ogawa, Yuji; Honda, Yasushi; Kessoku, Takaomi; Yoneda, Masato; Imajo, Kento; Tomeno, Wataru; Saito, Satoru; Nakajima, Atsushi
Abstract : Aim: The progression of non‐alcoholic fatty liver disease (NAFLD) is affected by epigenetics. We undertook co‐methylation and differentially methylated region (DMR) analyses to identify the genomic region that is under epigenetic regulation during NAFLD progression. Methods: We collected liver biopsy specimens from 60 Japanese patients with NAFLD and classified these into mild (fibrosis stages 0–2) or advanced (fibrosis stages 3–4) NAFLD. We carried out a genome‐wide DNA methylation analysis and identified the differentially methylated CpGs between mild and advanced NAFLD. Differentially methylated regions with multiple consecutive differentially methylated CpGs between mild and advanced NAFLD were extracted. Results: Co‐methylation analysis showed that individual differentially methylated CpG sites were clustered into three modules. The CpG sites clustered in one module were hypomethylated in advanced NAFLD and their annotated genes were enriched for "immune system" function. The CpG sites in another module were hypermethylated and their annotated genes were enriched for "mitochondria" or "lipid particle", and "lipid metabolism" or "oxidoreductase activity". Hypomethylated DMRs included tumorigenesis‐related genes ( FGFR2, PTGFRN, and ZBTB38 ), the expressions of which are upregulated in advanced NAFLD. Tumor suppressor MGMT had two DMRs and was downregulated. Conversely, FBLIM1 and CYR61, encoding proteins that reduce cell proliferation, showed hypomethylated DMRs and were upregulated. Expression of the antioxidant gene NQO1 was upregulated, with a hypomethylated DMR. The DMR containing cancer‐related MIR21 was hypomethylated in advanced NAFLD. Conclusions: Co‐methylation and DMR analyses suggest that the NAFLD liver undergoes mitochondrial dysfunction, decreased lipid metabolism, and impaired oxidoreductase activity, and acquires tumorigenic potential at the epigenetic level.